2019
DOI: 10.3390/molecules24213958
|View full text |Cite
|
Sign up to set email alerts
|

Allium sativum Extract Chemical Composition, Antioxidant Activity and Antifungal Effect against Meyerozyma guilliermondii and Rhodotorula mucilaginosa Causing Onychomycosis

Abstract: Onychomycosis is a major health problem due to its chronicity and resistance to therapy. Because some cases associate paronychia, any therapy must target the fungus and the inflammation. Medicinal plants represent an alternative for onychomycosis control. In the present work the antifungal and antioxidant activities of Alium sativum extract against Meyerozyma guilliermondii (Wick.) Kurtzman & M. Suzuki and Rhodotorula mucilaginosa (A. Jörg.) F.C. Harrison, isolated for the first time from a toenail onychomycos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…The main active compound isolated from Allium sativum has many biological effects, which have been demonstrated during the last decades. Its antioxidant, anti-inflammatory, immunostimulatory, and antifungal activities have been the study subjects for many research groups [16,36]. A constant intake of allicin via garlic consumption could reduce chronic inflammation, oxidative stress, and DNA damage [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main active compound isolated from Allium sativum has many biological effects, which have been demonstrated during the last decades. Its antioxidant, anti-inflammatory, immunostimulatory, and antifungal activities have been the study subjects for many research groups [16,36]. A constant intake of allicin via garlic consumption could reduce chronic inflammation, oxidative stress, and DNA damage [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Allicin was synthesized and characterized as reported in our previous work, and using the Mass Spectrometry (MS) and 1 H, and 13 C NMR analysis, we determined that allicin has a purity of more than 96% [16].…”
Section: Allicin Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Garlic extracts showed a broad spectrum fungicidal effect against a wide range of fungi including Candida, Torulopsis, Trichophyton, Cryptococcus, Aspergillus, Trichosporon, and Rhodotorula species. Recently, garlic extract was found to inhibit the Meyerozyma guilliermondii and Rhodotorula mucilaginosa germination and growth [55]. Another study reported the antifungal activity of various A. sativum extracts namely aqueous, ethanolic, methanolic, and petroleum ether against human pathogenic fungi such are Trichophyton verrucosum, T. mentagrophytes, T. rubrum, Botrytis cinerea, Candida species, Epidermophyton floccosum, Aspergillus niger, A. flavus, Rhizopus stolonifera, Microsporum gypseum, M. audouinii, Alternaria alternate, Neofabraea alba, and Penicillium expansum [56].…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Garlic is one of the most cultivated therapeutical plants [ 4 ]. The studies focused on the curative capacities of garlic highlighted its antioxidative properties [ 5 ], hypoglycemic and cardioprotective effects [ 6 , 7 ], anticancer [ 8 ], antifibrotic [ 9 ], and antifungal properties [ 10 ].…”
Section: Introductionmentioning
confidence: 99%